The New Pattern of Market Competition in the Era of Digital Economy: The Driving Factors of Innovation and Entrepreneurship - Zhang, Chenyu (International Journal of Global Economics and Management, 2024)
With the rapid evolution of information technology, digital economy has evolved into the core engine of global economic transformation, further subvert the existing market game situation, and bring profound reshaping of the traditional business environment. The goal of this article is to analyze the new landscape of market competition in this digital era and the key drivers of innovation and entrepreneurship. The article first defines the concept of digital economy and traces its evolution and current trend. We then discover the inherent constraints of traditional market competition mechanisms and illustrate how the digital revolution is reshaping competition paradigms and their uniqueness. Further, we look at four dimensions: technological innovation (such as artificial intelligence and big data, the application of blockchain), regulatory support (such as the innovation agenda of government departments and the improvement of the entrepreneurial ecosystem), fluctuations in consumer demand (including changes in shopper behavior and the emergence of new market opportunities), and capital flow mechanisms (such as venture capital, crowdfunding and innovative financing strategies). In-depth analysis of entrepreneurial driving force of multiple aspects. By comparing examples of successful companies with examples of failures, we extract some key operational insights and lessons. Finally, the paper Outlines the possible ways of future exploration, and gives a forward-looking outlook on the evolution of enterprise innovation in the digital economy. This study enriched the theoretical framework of digital economy, entrepreneurship, & innovation, offering both theoretical foundation & practical guidance, especially for devising efficient competitive strategies for enterprises in the digital era.